2011
DOI: 10.1002/lary.22273
|View full text |Cite
|
Sign up to set email alerts
|

Electrode deactivation in post‐meningitic cochlear implant recipients

Abstract: Objective:To assess the frequency of electrode deactivation over time in post meningitic cochlear implant (CI) recipients Study Design:Retrospective chart review Methods:A retrospective chart review of all post meningitic cochlear implant recipients at New York University from 1984 2008 was conducted. Patients with more than 2 years of follow up programming and speech perception data were included. Percent of active electrodes was calculated relative to maximum number of programmable electrodes. Frequency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Clinically, a CI electrode array is inserted into the scala tympani, one of the three cochlear ducts 13 (Fig.1a). As a coarse-grained approach to replicate the electroanatomical features of a CI implanted cochlea, we approximate the cochlea as one ensemble spiral cavity with continuously narrowing diameter, and omit the inner soft-tissue membranous structures of a cochlea, such as the basilar membrane and Reissner’s membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, a CI electrode array is inserted into the scala tympani, one of the three cochlear ducts 13 (Fig.1a). As a coarse-grained approach to replicate the electroanatomical features of a CI implanted cochlea, we approximate the cochlea as one ensemble spiral cavity with continuously narrowing diameter, and omit the inner soft-tissue membranous structures of a cochlea, such as the basilar membrane and Reissner’s membrane.…”
Section: Resultsmentioning
confidence: 99%
“…We anticipate that this unique capability might enable long-term monitoring of patients’ cochlear health after CI implantation. For example, it has been suggested that the electrical properties of cochlear tissues can be affected by a variety of physiological and otologic diseases, such as post-implantation fibrosis and neo-ossification, post-operative electrode extrusion and medications 13,49,50 . Hence, the cochlear tissue resistivities informed by patients’ EFI profiles might be used as a diagnostic indicator to detect early abnormalities, without resorting to ionizing radiation of patients (which particularly should be avoided in children).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this work has been performed in pediatric and mixed pediatric and adult populations (14). Furthermore, the largest analysis of patients with electrode deactivation for any reason was done in 1999 with 100 patients with Cochlear Nucleus CIs having at least 1 deactivated electrode (13).…”
mentioning
confidence: 99%